Pengaruh Performa Perusahaan Terhadap Kualitas Laporan Tanggung Jawab Sosial Perusahaan Yang Dimoderasi Oleh Tahap Siklus Hidup Perusahaan Pada Perusahaan LQ45 Periode 2017-2021 - Batubara, Satya Rifansyah; Danarsari, Dwi Nastiti (UI Scholars Hub, 2024)
This study aims to empirically prove the effect of corporate performance on the quality of corporate social responsibility (CSR) reports, moderated by the company's life cycle stages. The study uses a sample of companies listed in the LQ45 index as of August 2019, registered on the Indonesia Stock Exchange (IDX) for the period from 2017 to 2021. The method used in this study is pooled ordinary least squares (OLS) regression. The results show that corporate performance does not have a significant impact on CSR reports. However, firm life cycle stages have a significant effect with a negative correlation direction on CSR reports, and the impact of corporate performance on CSR reports is moderated by the firm's life cycle stages.